Students’ Perception Of Lecturers’ Teaching Performance - Achmad Firmansyah; Untung Waluyo; Azis, Atri Dewi (International Journal of Education, Language, Literature, Arts, Culture, and Social Humanities, 2023)
This research was about students’ perception of lecturers’ teaching performance at the English Department of FKIP Mataram University Academic Year 2020/2021. This research aims to discover the ideal teaching performances perceived by the students at the English Department of FKIP Mataram University. The method used in this research is descriptive quantitative design. The samples of this study totaled 70 students taken from the fifth, seventh, and ninth semesters. This research used a questionnaire as means of collecting the data. The researcher used a descriptive quantitative method for analyzing and presenting the data gathered from the questionnaire. The result from this research showed that the students at the English Department of FKIP Mataram University gave a significant amount of response in lecturers’ inventiveness (71.4%), lecturers’ preparedness (65.7%), lecturer’ classroom management (62.9%), and lecturers’ clarity of scoring rubric (54.4%). In addition, this study also discovers that the students at the English Department of FKIP Mataram University expected their lecturers to have a vast knowledge of the material subject, be friendly toward the students, have knowledge and ability in I.T. Lastly, the lecturers should be more understanding toward the students. The students in this study responded positively to the lecturers' teaching performance, which impacts their learning motivation and academic results.